Antibody-targeted horseradish peroxidase associated with indole-3-acetic acid induces apoptosis in vitro in hematological malignancies - Dalmazzo, Leandro F. F.; Santana-Lemos, Barbara A.; Jacomo, Rafael H.; Garcia, Aglair B.; Rego, Eduardo M.; da Fonseca, Luiz M. [UNESP]; Falcao, Roberto P. (Pergamon-Elsevier B.V. Ltd, 2011)
Indole-3-acetic acid (IAA), when oxidized by horseradish peroxidase (HRP), is transformed into cytotoxic molecules capable of inducing cell injury. The aim of this study was to test if, by targeting hematopoietic tumors with HRP-conjugated antibodies in association with IAA treatment, there is induction of apoptosis. We used two lineages of hematologic tumors: NB4, derived from acute promyelocytic leukemia (APL) and Granta-519 from mantle cell lymphoma (MCL). We also tested cells from 12 patients with acute myeloid leukemia (AML) and from 10 patients with chronic lymphocytic leukemia (CLL). HRP targeting was performed with anti-CD33 or anti-CD19 antibodies (depending on the origin of the cell), followed by incubation with goat anti-mouse antibody conjugated with HRP. Eight experimental groups were analyzed: control, HRP targeted, HRP targeted and incubated with 1, 5 and 10 mM IAA, and cells not HRP targeted but incubated with 1, 5 and 10 mM IAA. Apoptosis was analyzed by flow cytometry using annexin V-FITC and propidium iodide labeling. Results showed that apoptosis was dependent on the dose of IAA utilized, the duration of exposure to the prodrug and the origin of the neoplasia. Targeting HRP with antibodies was efficient in activating IAA and inducing apoptosis. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: 3-Indole-acetic acid; Horseradish peroxidase; Apoptosis; Acute myeloid leukemia; Chronic lymphocytic leukemia